Determination of Monochloroacetic Acid in Swimming Pool Water by Ion Chromatography-Conductivity Detection - Espino, Maria Pythias B.; Mendoza, Jamie P. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 25 No 2 (2013))
In this study, an analytical method involving ion chromatography with conductivity detection was developed and optimized for the determination of monochloroacetic acid in swimming pool water. The ion chromatographic method has a detection limit of 0.02 mg L-1 and linear range of 0.05 to 1.0 mg L-1 with correlation coeff icient of 0.9992. The method is reproducible with percent RSD of 0.052% (n=10). The recovery of monochloroacetic acid spiked in different water types (bottled, tap and swimming pool water) ranged from 28 to 122%. In dilute solutions, chloride and bromide were simultaneously analyzed along with monochloroacetic acid using the optimized method. Chloride and bromide have detection limits of 0.01 to 0.05 mg L-1, respectively. The usefulness of the ion chromatographic method was demonstrated in the analysis of monochloroacetic acid in swimming pool water samples. In such highly-chlorinated samples, an Ag/H cartridge was used prior to the ion chromatographic determination so as to minimize the signal due to chloride ion. Monochloroacetic acid was detected in concentrations between 0.020 and 0.093 mg L-1 in three of the six swimming pool water samples studied. The presence of monochloroacetic acid in the swimming pool water samples suggests the possible occurrence of other disinfection by-products in these waters. Keywords: Monochloroacetic acid, chloride, bromide, water, ion chromatography